Lactic acid bacterial surface display of scytovirin inhibitors for anti-ebolavirus infection - Wiggins, Joshua; Nguyen, Ngan; Wei, Wenzhong; Wang, Leah Liu; Hollingsead Olson, Haley; Xiang, Shi-Hua (Frontiers in Microbiology, 2023)
Scytovirin (SVN) is a lectin from cyanobacteria which has a strong inhibitory activity against Ebola virus infection. We engineered scytovirin as the inhibitor for surface display of lactic acid bacteria to block Ebola virus infection. Two different bacterial strains (Lactobacillus casei and Lactococcus lactis) were successfully engineered for scytovirin expression on the bacterial surface. These bacteria were found to be effective at neutralizing pseudotyped Ebolavirus in a cell-based assay. This approach can be utilized for prophylactic prevention, as well as for treatment. Since lactic acid bacteria can colonize the human body, a long-term efficacy could be achieved. Furthermore, this approach is also simple and cost-effective and can be easily applied in the regions of Ebola outbreaks in the developing countries.